Supracostal Percutaneous nephrolithotomy, a safe and effective approach: a clinical audit - Ali Haider; Syed Mamun Mahmud (Journal of the Pakistan Medical Association, 2022)
Objective: To emphasize on safety principles through anatomic approach in Supracostal PCNL Methods: Data of patients who underwent PCNL from June 2004 to August 2014 from The Kidney Centre Karachi, Pakistan were reviewed. Patients above 14 years of age were included. Supracostal Access were included in study. PCNL performed in Prone position with ‘Bull’s Eye Technique’. Nephrostomy were placed after the completion of procedure in most cases. Data regarding demographic details, stone burden, Stone clearance with primary PCNL and combination. And complications rate was also assessed over Modified Clavien Grades 1 through 5. Results: Total of 426 patients underwent PCNL. Seventy (70) out of 426 underwent PCNL through Supracostal Approach. Fifty (71.4 %) patients were Stone Free after PCNL and Sixty Four (91.4%) Patients were stone free after auxiliary procedures (ESWL, SECONDARY PCNL). The overall complication rate was 4.7% with 3 (4.3%) patients required Tube Thoracostomy. One (1.4%) each for angioembolization, pulmonary edema/Ventilation and ICU admission for urosepsis and renal dysfunction. Conclusion: Supracostal PCNL is a safe and effective approach for pelvicalyceal system having multiple stones. Due anatomic consideration can decrease the complication rate. In complex stones with huge burden, an elaborate and thorough counseling regarding delayed clearance, need for auxiliary procedures including Secondary PCNL is mandatory. Keywords: PCNL, Supracostal, Anatomic Perspective and Complications. Continuous...